2018
DOI: 10.1007/s00520-018-4067-7
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of sustainability in healthcare systems: frequency and cost of diagnostic procedures in end-of-life cancer patients

Abstract: BackgroundLiterature data on the overuse and misuse of diagnostic procedures leading to end-of-life aggressiveness are scarce due to the limited amount of estimated economic waste. This study investigated the potential overuse of diagnostic procedures in a population of end-of-life patients.MethodsThis is a retrospective study on consecutive advanced patients admitted into two Italian hospices. Frequency and relative costs of X-ray imaging, CT scans, MRI, and interventional procedures prescribed in the 3 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…In once recent study 258 it was reported that 57•4% of patients with metastatic lung, and 79•8% of patients with metastatic colorectal cancer believed that their surgery was likely to have been curative. Moreover there is also evidence that patients with advanced cancer are subject to increasing numbers of radiological investigations 259 and to a higher frequency of artificial nutritional support even in the context of decreased SACT. 260 Predicting survival in advanced cancer using prognostic tools Accurate staging can provide valuable prognostic information; can guide decision making about treatments at the individual patients level; allows for a common international terminology so that different centres can accurately describe the case-mix of their patients and can compare outcomes; and is essential for identifying homogenous populations for entry into clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…In once recent study 258 it was reported that 57•4% of patients with metastatic lung, and 79•8% of patients with metastatic colorectal cancer believed that their surgery was likely to have been curative. Moreover there is also evidence that patients with advanced cancer are subject to increasing numbers of radiological investigations 259 and to a higher frequency of artificial nutritional support even in the context of decreased SACT. 260 Predicting survival in advanced cancer using prognostic tools Accurate staging can provide valuable prognostic information; can guide decision making about treatments at the individual patients level; allows for a common international terminology so that different centres can accurately describe the case-mix of their patients and can compare outcomes; and is essential for identifying homogenous populations for entry into clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…However, the overuse of medical imaging in dying patients with cancer increase costs and postpone hospice referrals. 36,37 Our findings also highlight the importance of medical data integration between outpatient and inpatient providers. In the community setting, medical records are sometimes paper-based and not well integrated resulting in poor information sharing and duplicate medical imaging.…”
Section: Discussionmentioning
confidence: 59%
“…17 This may be particularly relevant for limited-resource countries because the overuse of medical imaging in the last phase of life significantly increases health-care spending, despite questionable therapeutic benefits. 18 Our results indicated that more than a half of patients were admitted to ICU in the last 30 days of life. Over the last decade, therapeutic advances and better survival rates for the critically ill patient with HM have resulted in broader ICU admission policies around the world, including in Brazil.…”
Section: Discussionmentioning
confidence: 62%
“…24 We identified that 10% of patients used ARRT near death. Although the diagnosis of HM by itself is not a reason to withhold ARRT, 25 hemodialysis is associated with increased health-care costs, longer length of stays, 11 (16) 16 (18) .16…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation